Avaliação pós-ocupação na escola de música e artes cênicas da Universidade Federal de Goiás ambiente construído e comportamento humano - MENDONÇA, Ana Domitila de Almeida (2011)
This paper seeks to apply the system of Post-Occupancy Evaluation in the School of Music and Scenic Arts of Federal University of Goiás. The methodology included detailed characterization of the area investigated, with the steps: familiarization object of study, quantitative and qualitative research, data analysis and proposed improvements on the same subject of study as a place of work, learning and living in society. Data analysis gave the direction to a deepening in the acoustic issues and Needs Program that took shape during the search. First, due to the fact the school coves the courses of Music and Music Therapy, and second, due the fact coves courses for the Scenic Arts and Art Director and Producer that in front of the specificities of its growth and its physical characteristics of its facilities, located is in need of expansion and favorable places for them, attending to their peculiarities. Among the techniques of data collection used in Post-Occupancy Evaluation, Walkthrough happened with the monitoring of maintenance workers allowed a new look to the building and may contribute to reflections, retro-projective feeding decisions. Quantitative research, from the use questionnaires, revealed the profiles of their users and how they connect space, built or not; over there can assess the performance of the building. Qualitative research, by using the technique of the interviews and employment tool called "Poem of Desire" came elucidate the wishes of users and inter-personal relationships. For realize these reflections was used interdisciplinary, which allows the researcher to walk through different areas of knowledge. In front of the results have been proposed guidelines for projects and proposals for reform of preliminary study and the studies of new buildings to shelter the Laboratories of Scenic Arts and, another for isolated smalls room, for the study of musical instruments. These proposals have emerged in syntony with the aspirations of users to ensure them a higher level of satisfaction. The case study showed that, today, this type of evaluation has evolved into a dynamic model that makes it clear that at the end of each cycle of implementation of proposed interventions, the time will also be re-evaluated along with their users as spiral system.